Axial prestretch and circumferential distensibility in biomechanics of abdominal aorta - Horný, Lukáš; Netušil, Marek; Voňavková, Tereza (Biomechanics and modeling in mechanobiology, 2014)
Elastic arteries are significantly prestretched in an axial direction. This property minimises axial deformations during pressure cycle. Ageing-induced changes in arterial biomechanics, among others, are manifested via a marked decrease in the prestretch. Although this fact is well known, little attention has been paid to the effect of decreased prestretch on mechanical response. Our study presents the results of an analytical simulation of the inflation-extension behaviour of the human abdominal aorta treated as nonlinear, anisotropic, prestrained thin-walled as well as thick-walled tube with closed ends. The constitutive parameters and geometries for 17 aortas adopted from the literature were supplemented with initial axial prestretches obtained from the statistics of 365 autopsy measurements. For each aorta, the inflation-extension response was calculated three times, with the expected value of the initial prestretch and with the upper and lower confidence limit of the initial prestretch derived from the statistics. This approach enabled age-related trends to be evaluated bearing in mind the uncertainty in the prestretch. Despite significantly decreased longitudinal prestretch with age, the biomechanical response of human abdominal aorta changes substantially depending on the initial axial stretch was used. In particular, substituting the upper limit of initial prestretch gave mechanical responses which can be characterised by (1) low variation in axial stretch and (2) high circumferential distensibility during pressurisation, in contrast to the responses obtained for their weakly prestretched counterparts. The simulation also suggested the significant effect of the axial prestretch on the variation of axial stress in the pressure cycle. Finally, the obtained results are in accordance with the hypothesis that circumferential-to-axial stiffness ratio is the quantity relatively constant within this cycle.
Keywords: senioři; biomechanika; Models, Cardiovascular; modely kardiovaskulární; Reproducibility of Results; Aging; Anisotropy; pitva; krevní tlak; reprodukovatelnost výsledků; Male; Computer Simulation; Aorta; počítačová simulace; Elasticity; arterie; lineární modely; Biomechanical Phenomena; Middle Aged; mužské pohlaví; aorta; Aorta, Abdominal; tlak; Pressure; Adult; Stress, Mechanical; anizotropie; systola; Diastole; diastola; pružnost; Linear Models; stárnutí; ženské pohlaví; Blood Pressure; Humans; lidé středního věku; Systole; mechanický stres; dospělí; Female; Aged; Arteries; lidé; aorta abdominalis; Autopsy